(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
Noise pollution is an increasingly pressing issue in urban areas around the world, including Onitsha, Nigeria. This study aims to assess the noise pollution levels in the several districts of Onitsha such as Onitsha main market, Awada, Fegge, Okpoko, Inland town, Woliwo and GRA, through identifying the hot spots and taking the noise readings using the sound level meter, calculating the noise levels using the decibel models and to analyse the results to identify the noise situation of the city. Through a combination of field measurements, surveys, evaluations and literature review, this research provides a comprehensive overview of the noise pollution problem in Onitsha and suggests practical solutions to mitigate its effects. Results show that districts like Onitsha main market, Woliwo, Awada, etc., have unsatisfactory daytime levels of noise of 90.2db, 89.8db, 84.8db respectively, only GRA have a noise level that is satisfactory (76.6db), hence, to control this unsatisfactory noise levels a control measure are outlined and recommendations given.